Knowing the Potential of Geometry as a Support Tool of the Curriculum Implementation with Competition Based in the Secondary School - Ibnu Ngatoillah (Universitas Muhammadiyah Semarang, 2004)
The purpose this article is to show the effect of geometry as one of the mathematical topies in the secondary school as a tool in supporting the curriculum implementation with competition based.By using many opinions about geometry, we hope that teachers can do hardly to show the potential of geornetry. It means to know what kind of aspects that must be to develop by teacl